Очерки по историографии декабристов - Парадизов Петр Павлович (Московский рабочий, 1928)
Экземпляры: КХ (20100430) / Инвентарный номер: д18910 / Цена: 2.75 / Сис.шифр: 63.3(2)4 / Авт.знак: П 18 / ГРНТИ: 03 / ББК: 63.3(2)521-425